Credit availability and classification shifting: Based on the quasi-natural experiment of the bank lending interest rate ceiling deregulation - Jingru Wang; Hongjian Wang; Xinghe Liu; Qingyuan Li (China Journal of Accounting Studies (CJAS), 2022)
Based on the exogenous shock of the bank lending interest rate ceiling deregulation in China, this paper uses a difference-in-differences model and studies how credit availability affects classification shifting from the perspective of formal debt contract formation. We find that high-risk firms' classification shifting degree is higher after the bank lending interest rate ceiling deregulation. Cross-sectional heterogeneity tests show that the impact of the deregulation on classification shifting is stronger when the level of financing constraints is higher, the diversity of financing channels is lower, the bank's need for information is higher, and the bank's monitoring is higher. Mechanism tests further show that the deregulation enables high-risk firms to increase borrowing through classification shifting. We use the unique setting of China interest rate liberalisation to scientifically identify the debt financing motivation for classification shifting. This study expands and enriches the institutional determinants of accounting information production.
Keywords: 650; Interest rate liberalisation; debt contract; core earnings; classification shifting